Modeling the Flow Dynamics of the Langjökull Ice Cap, Iceland - Robinson, Rebecca Anne, 1990- (2018)
The ice flow dynamics of the Langjökull ice cap have been explored using the Parallel Ice Sheet Model (PISM). Although PISM was developed mainly for the purpose of exploring the flow dynamics of large ice sheets, it can be forced with data sets from smaller ice caps and used as a numerical tool for understanding ice flow over comparatively smaller spatial scales. The data used to force PISM were collected between the years of 1997--2016. Measured bedrock and surface topographies are used as boundary conditions for the model. Interpolated temperature and mass balance maps were created for the Langjökull ice cap and used as forcing for PISM. A series of model runs are carried out, each initialized with constant mass balance and annual temperature means. By running the model forward 500 years with individual annual means between 1997 and 2016 as well as the overall mean for the period, a range of steady state geometries for Langjökull are found. Model output was compared with data along a flow line following Vestari-Hagafellsjökull, which has a history of surging and was used for model validation due to the wealth of data available along the flowline there. Model-data comparison reveals that some climate forcings produce results that fit within the range of measurements, but some forcings result in velocities that are far too high. The sliding law was modified in order to control the locations where sliding is allowed to occur by making the till friction angle dependent on elevation. It was found that the modified sliding law gives results that fit well with the measurements of surging velocities. In this report, model results are presented and the model sensitivity to changes in the forcing is discussed. The balance velocity is analyzed within the context of the measured velocity and potential causes for surges of Vestari-Hagafellsjökull are explored. Flæði Langjökuls var rannsakað með því að beita líkaninu PISM (Parallel Ice Sheet Model) með upphafs- og jaðarskilyrðum sem byggja á mælingum frá jöklinum. Þótt ...